Tunable visible photoluminescence of powdered silica glass - Pizani, P. S.; Joya, M. R.; Pontes, Fenelon Martinho Lima [UNESP]; Santos, L. P. S.; Godinho, M.; Leite, E. R.; Longo, Elson [UNESP] (Elsevier B.V., 2008)
intense photoluminescence in the visible region was observed at room temperature in standard soda-lime-silica glass powder, mechanically milled in a high-energy attrition mill. The emission band maximum shows an interesting dependence on the exciting wavelength, suggesting the possibility to tune the PL emission. These findings indicate that the photoluminescence may be directly related to unsatisfied chemical bonds correlated with the high surface area. The Raman scattering and ultraviolet-visible optical reflectance measurements corroborate this assertion. Transmission electron microscopy measurements indicate that samples milled more than 10 h present the formation of nanocrystallites with about 10-20 nm. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Raman scattering; luminescence; soda-lime-silica; short-range order